Phylogeography of Holothuria (Halodeima) inornata Semper, 1868 (Echinodermata: Holothuroidea) - Prieto-Rios, Elba (2014)
Genetic structure of the populations of H. inornata was evaluated and the barriers for genetic flux and historic processes were investigated. Samples were collected trying to cover the distribution range of the species, from Mexico to northern Perú. Based on COI sequences, 118 haplotypes from 220 specimens were detected; the differences between such haplotypes were due to 97 variable sites (21.41%) of the 453 bp sequenced. A high haplotype diversity (h=0.979) and a moderate nucleotidic diversity were observed. The values of Fst, the exact test of population differentiation, and the molecular variance analysis (AMOVA) were used in order to analyze the genetic differentiation. These analyses suggest the existence of two populations: northern, off the coasts of Sinaloa, Jalisco, Michoacán, Guerrero, and Oaxaca, and southern, off the coasts of Chiapas, El Salvador, Panamá and Perú. Historic events and oceanographic patterns may be the main factors determining dispersion and structure of Hi populations. It seems probable that the original population have extended first in the south and then northern. Besides, the split between these two populations may be due to several tectonic and oceanographic events constituting a barrier for H. inornata settling.